MODEL PENGAJARAN TERBALIK DALAM MATA KULIAH CHUKYU DOKKAI - Amira Agustin Kocimaheni (Universitas Negeri Surabaya, 2015)
Chukyu Dokkai lecture is an intermediate reading lecture which the students program after taking the Shokyu Dokkai, an elementary reading lecture. In the elementary level of reading a lecturer still takes a very great role in the teaching and learning process. The roles includes guiding and teaching the students to read starting from words, sentences, paragraph and even the lecturer still use the translation method. But not for the intermediate level of reading, the methods and techniques of the teaching is more various. One of the models which can be used is reciprocal teaching. This model puts the teacher or lecturer as a model and facilitator than a presenter of the teaching and learning process. The students are taught four strategies of specific self-understanding and control, namely summarizing, questioning, clarifying, and predicting. While the teaching and learning process is taking place, the students are actively involved in the discussion in their groups. The lecturer acts as mediator, model, and trainer. The teaching and learning process will not be a one way process where the lecturer controls the process, but the students will also have the chance to give their opinions. Therefore it is hoped that the students will grow the responsibility within them and the lecturer will stay with them to help them monitor, think and choose the strategy that can be used in the process of studying